2009
DOI: 10.2214/ajr.07.7102
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Characteristics of Diffuse Idiopathic Skeletal Hyperostosis With an Emphasis on Acute Spinal Fractures:Review

Abstract: Understanding the pathomechanics of the fractures in the ankylosed spine is important in the differentiation of the acute spinal fractures in DISH and ankylosing spondylitis. This article emphasizes the imaging features of spinal DISH and acute spinal fractures in DISH, distinguishing them specifically from those in ankylosing spondylitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Resnick and Niwayama found T7 to T10 level involvement in both sides [14] and Talijanovic et al observed and stated that most commonly involved region is thoracic vertebrae, in that particularly 7th thoracic to 11th thoracic vertebrae are involved more frequently than any other [15]. In the current study bilateral ossification was seen in the thoracic level in 2 specimens.…”
Section: Discussionsupporting
confidence: 61%
“…Resnick and Niwayama found T7 to T10 level involvement in both sides [14] and Talijanovic et al observed and stated that most commonly involved region is thoracic vertebrae, in that particularly 7th thoracic to 11th thoracic vertebrae are involved more frequently than any other [15]. In the current study bilateral ossification was seen in the thoracic level in 2 specimens.…”
Section: Discussionsupporting
confidence: 61%
“…Fractures in patients with ASD often resulted from trivial trauma, for example, falls from a standing or sitting position, possibly causing some physicians to underestimate injury severity. Difficult interpretation of radiological examinations showing gross pre-existent pathologic changes to the spine could also be responsible for this phenomenon [25]. When a fracture is suspected in the absence of traumatic abnormalities on conventional radiographs or computed tomography, a magnetic resonance imaging scan (with focus on T2 and STIR sequences) should be performed to minimize the risk of missing occult fractures [26].…”
Section: Discussionmentioning
confidence: 99%
“…These injuries are very common in individuals with degenerated or ankylosed spines—as seen in ankylosing spondylitis and diffuse hypertrophic skeletal hyperosteosis (DISH)—even with relatively minor trauma [35]. …”
Section: Common Injury Patternsmentioning
confidence: 99%